Room temperature processed in-situ carbon-coated vanadium carbide (VC@C) as a high capacity robust Li/Na battery anode material - Mahajan, Mani; Roy, Kingshuk; Parmar, Swati; Singla, Gourav; Pandey, O. P.; Singh, K.; Vaidhyanathan, Ramanathan; Ogale, Satishchandra (Carbon, 2020)
3D carbide systems with their robust physical and mechanical properties have always attracted multiple application interests. In this report, we have synthesized a three-dimensional in-situ carbon coated cubic carbide, Vanadium Carbide (VC@C), by a very simple, scalable and cost-effective room temperature mechano-chemical ball-milling procedure and researched its promise as effective anode material for Li and Na ion batteries. We have demonstrated that VC@C shows an impressive initial discharge/lithiation capacity of 1165 mAh g(-1) with a high reversible capacity of 640 mAh g(-1) after 100 charge-discharge cycles at an applied current density of 0.1 A g(-1). We have also found that this material renders a very promising rate performance with significantly low capacity drop after exposing it to variable current densities ranging from 0.05 A g(-1) to 2 A g(-1) with an excellent stability up to 1000 cycles owing to its structural robustness, as verified by post-cycling characterizations. A Li-ion full cell study using LiCoO2 as cathode also showed excellent promise in terms of practical application demonstrating a reversible capacity of 95 mAh g(-1) after 100 cycles. Even for Na insertion/de-insertion VC@C shows a clear promise in terms of capacity, cyclic stability and rate performance. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 3D carbide; In-situ synthesis; Li-ion battery; Post cycling characterization; Room temperature ball milling; Williamson-Hall analysis

Resorcinol-Azodianiline Covalent Organic Framework Supported FeOOH Quantum Dot-Catalyzed Electrochemical Ammonia Synthesis under Ambient Conditions - Shekhar, Pragalbh; Kosugi, Kento; Singh, Himan Dev; Kushwaha, Rinku; Rase, Deepak; Matsuzaki, Takumi; Jain, Chitvan; Singh, Piyush; Singh, Yashraj; Vinod, Chathakudath Prabhakaran; Kondo, Mio; Masaoka, Shigeyuki; et al. (CHEMISTRY OF MATERIALS, 2024)
Keywords: conversion; nitrogen; Recent Progress; reduction